KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN PADA OPTIK DI SUMATERA BARAT - Wesnita, Alvia; Elfia, Mega; Amril, Alwa Pascaselnofra (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Satisfaction is the level of feeling after comparing perceived performance with expectations (Philip Kotler, 1997, 36). So a company must pay attention to the things that are considered important by customers so that their expectations are met. Quality of service is centered on efforts to fulfill customer needs, such as accuracy in inspection, conformity of product specifications and processing time provided according to order as well as friendly service from each personnel. The results of the study A total of 15 respondents (50%) are very satisfied and 15 respondents (50%) are satisfied with the effectiveness of the service and as many as 15 respondents (50%) are very satisfied and 15 respondents (50%) are satisfied with the efficiency of optical services in West Sumatra. Based on the results of this study, there are several suggestions that need to be submitted, namely: (1) Researchers must understand and be able to explain and be able to apply the implementation of service effectiveness and efficiency to customer satisfaction (2) Optical in order to implement the implementation of service effectiveness and efficiency on satisfaction customers, and an optical refraction check should be carried out by an Optimist Refractionist and (3) the public so that they can choose and make glasses with maximum service and results so that satisfaction is achieved.